2012
DOI: 10.1128/mcb.06373-11
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase KDM5B Collaborates with TFAP2C and Myc To Repress the Cell Cycle Inhibitor p21 cip ( CDKN1A )

Abstract: The TFAP2C transcription factor has been shown to downregulate transcription of the universal cell cycle inhibitor p21 cip (CDKN1A). In examining the mechanism of TFAP2C-mediated repression, we have identified a ternary complex at the proximal promoter containing TFAP2C, the oncoprotein Myc, and the trimethylated lysine 4 of histone H3 (H3K4me3) demethylase, KDM5B. We demonstrated that while TFAP2C and Myc can downregulate the CDKN1A promoter independently, KDM5B acts as a corepressor dependent on the other tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…1D). As positive controls ChIPs of CDKN1a, coding for the cell cycle inhibitor p21 22 , and dihydrofolate reductase (DHFR) 23 that are c-Myc target genes were included. Of note, we detected even higher levels of binding of c-Myc and Max to the B7-H6 gene as compared to the positive controls.…”
Section: Resultsmentioning
confidence: 99%
“…1D). As positive controls ChIPs of CDKN1a, coding for the cell cycle inhibitor p21 22 , and dihydrofolate reductase (DHFR) 23 that are c-Myc target genes were included. Of note, we detected even higher levels of binding of c-Myc and Max to the B7-H6 gene as compared to the positive controls.…”
Section: Resultsmentioning
confidence: 99%
“…25 Wong et al reported that KDM5B collaborates with TFAP2C and Myc to suppress the cell cycle inhibitor p21 cip . 26 Enkhbaatar et al reported that ectopic expression of KDM5B promotes epithelial-mesenchymal transition (EMT) of cancer cells. 27 Li et al reported that KDM5B is highly expressed in prostate cancer cells and promotes proliferation and inhibits apoptosis of prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…KDM5B-mediated histone H3K4 demethylation contributes to the silencing of retinoblastoma target genes in senescent cells, presumably by compacting chromatin and silencing certain genes [13,14]. Previous studies have found that KDM5B depletion stimulated p16 and p21 transcription and suppressed tumor cell growth in vitro and in vivo [15,16], suggesting that it plays a role in cell growth regulation in human cancer.…”
Section: Introductionmentioning
confidence: 99%